ChemInform Abstract: Synthesis of Enantiopure Furo[2, 3‐b]pyrroles. Issue 15 (April 2015) - Nair, Divya S.; Ibnusaud, Ibrahim
Abstract: This diastereo‐ and enantioselective synthesis of dihydroxyhexahydrofuro[2, 3‐b]pyrrolones comprises the preparation of the key structural element of physovenine, madindoline and diazoamide A.